2014
DOI: 10.1007/s00784-014-1368-1
|View full text |Cite
|
Sign up to set email alerts
|

Ridge preservation using a new 3D collagen matrix: a preclinical study

Abstract: The use of the new collagen matrix associated with a collagen membrane could be a clinical option to preserve post-extraction ridges, especially when an improvement in soft tissue dimension and quality is desired. However, the cost-benefit ratio of this approach should be thoroughly evaluated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…No benefit of ridge preservation was observed on the soft tissue level at the day of implant placement compared to sites with spontaneous healing. This is in line with previous reports for spontaneous healing or using a collagen matrix as socket seal following a longer healing period (Jung et al 2013, Lindhe et al 2014, Roman et al 2015.…”
Section: Discussionsupporting
confidence: 93%
“…No benefit of ridge preservation was observed on the soft tissue level at the day of implant placement compared to sites with spontaneous healing. This is in line with previous reports for spontaneous healing or using a collagen matrix as socket seal following a longer healing period (Jung et al 2013, Lindhe et al 2014, Roman et al 2015.…”
Section: Discussionsupporting
confidence: 93%
“…Collagen barriers also have some specific physicochemical properties, including hemostatic activity that allows wound stabilization, chemotactic effects over gingival fibroblasts, and permeability that allows nutrient transfer [23]. Considering the ease of manipulation, decreased risk of flap dehiscence, and low immunogenicity associated with these membranes, they are the ideal barrier materials for socket preservation [24]. An important concern related to the use of bioabsorbable membranes is the speed at which resorption takes place.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…Moreover, Roman et al (27) used collagen membranes and 3D collagen matrices for ridge preservation with no comparison to natural healing. They concluded that collagen plugs showed biologically favorable responses in the healing event, use of collagen matrix alone might have limited effect on maintaining ridge dimension.…”
Section: Discussionmentioning
confidence: 99%